Comparison between the modified long gonadotropin-releasing hormone agonist protocol and the non-downregulation protocol in POSEIDON groups: a propensity score matching retrospective cohort study - Chen, Chunyan; Zeng, Xinliu; Zhang, Hanke; Wei, Qiongqiong; Gao, Ying; Liu, Lin (Frontiers in Endocrinology, 2023)
Background In vitro fertilization (IVF) is the main technique to address the infertility issue in the patient-oriented strategy encompassing individualized oocyte number (POSEIDON) population. Adopting appropriate protocols for assisted reproduction technologies (ART) cycles in the POSEIDON group may attain more favorable pregnancy outcomes. Objectives This study aimed to compare the effectiveness of modified long gonadotropin-releasing hormone agonist protocol and non-downregulation protocol in POSEIDON patients undergoing ART, and to identify the factors affecting the pregnancy outcomes in this group. Design This study was designed as a propensity score-matched (PSM) retrospective analysis. Participants The study cohort consisted of 910 patients diagnosed with ovarian hyporesponsiveness and treated by IVF from January 2020 to June 2022. They were followed up until the transfer of the last embryo of the IVF cycle and/or pregnancy at 12 weeks. The study was conducted at the Center of Reproductive Medicine, Tongji Medical College, Wuhan Union Hospital, Huazhong University of Science and Technology. Methods The patients were divided into Group I and Group II. Group I was treated with modified long gonadotropin-releasing hormone agonist protocol while Group II was put on a non-downregulation protocol. Propensity score matching (PSM) was used to select patients for each group. The subjects were compared in terms of the baseline level, process of controlled ovarian hyperstimulation, and pregnancy outcomes. Binary logistic regression analysis was performed to assess the difference in the cumulative pregnancy rate between the two groups. Results Of the 910 POSEIDON patients who underwent IVF, 213 received the modified long gonadotropin-releasing hormone agonist protocol and 697 were subjected to the non-downregulation protocol. From the original cohort, PSM matched 174 pairs of patients. No statistically significant difference was found in total gonadotropin (Gn) dose between the two PSM groups, but the average daily Gn dose was lower in Group I and the duration of Gn lasted longer. The number of retrieved oocytes, the number of metaphase II (MII) ooctyes retrieved, normal fertilization, and normal cleavage embryos was significantly higher in Group I than in Group II, but there existed no significant difference in the number of high-quality embryos between the two groups. The single-cycle CPR (cumulative pregnancy rate) was higher in Group I than in Group II (for Group I: before PSM, CPR = 52.6%; after PSM, CPR = 51.7%; for Group II: before PSM, CPR = 34.0%; after PSM, CPR = 34.5%), and the difference was statistically significant. A binary logistic regression analysis in the unmatched patients showed that the CPR of Group II was 0.486 times that of Group I (95% CI: 0.303 to 0.779). Conclusions The modified long gonadotropin-releasing hormone agonist protocol can be used as an optimal protocol for IVF or ICSI (Intracytoplasmic sperm injection) in POSEIDON patients. Level of evidence Level III